Post-exercise recovery of biological, clinical and metabolic variables after different temperatures and durations of cold water immersion: A randomized clinical trial - Vanderlei, Franciele M. [UNESP]; De Albuquerque, Maíra C. [UNESP]; De Almeida, Aline C. [UNESP]; MacHado, Aryane F. [UNESP]; Netto, Jayme [UNESP]; Pastre, Carlos M. [UNESP] (Edizioni Minerva Medica, 2017)
BACKGROUND: Cold water immersion (CWI) is a commonly used recuperative strategy. However there is a lack of standardization of protocols considering the duration and temperature of application of the technique and the stress model. Therefore it is important to study the issue of dose response in a specific stress model. Thus the objective was to analyze and compare the effects of CWI during intense post-exercise recovery using different durations and temperatures of immersion. METHODS: One hundred and five male individuals were divided into five groups: one control group (CG) and four recovery groups (G1: 5' at 9±1 °C; G2: 5' at 14±1 °C; G3: 15' at 9±1 °C; G4: 15' at 14±1 °C). The volunteers were submitted to an exhaustion protocol that consisted of a jump program and the Wingate Test. Immediately after the exhaustion protocol, the volunteers were directed to a tank with water and ice, where they were immersed for the recovery procedure, during which blood samples were collected for later lactate and creatine kinase (CK) analysis.Variables were collected prior to the exercise and 24, 48, 72, and 96 hours after its completion. RESULTS: For the CK concentration, 15 minutes at 14 °C was the best intervention option, considering the values at 72 hours after exercise, while for the moment of peak lactate an advantage was observed for immersion for 5 minutes at 14 °C. Regarding the perception of recovery, CWI for 5 minutes at 14 °C performed better long-term, from the time of the intervention to 96 hours post-exercise. For pain, no form of immersion responded better than the CG at the immediately post-intervention moment. CONCLUSIONS: There were no differences in behavior between the CWI intervention groups for the outcomes studied.
Keywords: Creatine kinase; Cryotherapy; Immersion; Lactates; Recovery of function